Double-balloon enteroscopy for retrieving retained small-bowel video capsule endoscopes: a systematic review. (2nd January 2020) - Gao, Ye; Xin, Lei; Wang, Yu-Xin; Dong, Yuan-Hang; Liao, Zhuan; Li, Zhao-Shen; Du, Yi-Qi
Abstract: Background and aim: Capsule retention is the most common adverse event associated with video capsule endoscopy. The use of double-balloon enteroscopy-assisted capsule endoscope retrieval has been increasingly reported in recent years. However, evidence is limited regarding its success rate, associated factors, and subsequent clinical outcomes. Methods: A systematic review of relevant studies published before January 2019 was performed. Successful retrieval rate and associated factors, rate of endoscopic balloon dilation, and outcomes after double-balloon enteroscopy were summarized and pooled. Results: Within 154 associated original articles, 12 including 150 cases of capsule retrieval by double-balloon enteroscopy were included. The estimated pooled successful retrieval rate was 86.5% (95% confidence interval, 75.6–95.1%). Anterograde approach and capsules retained in the jejunum or trapped by malignant strictures were associated with a higher successful retrieval rate than the retrograde approach (62/83 [74.7%] vs. 10/38 [26.3%], p  < .001) and capsules retained in the ileum (41/41 [100.0%] vs. 43/58 [74.1%], p  < .001) or trapped by benign strictures (21/21 [100.0%] vs. 65/83 [78.3%], p  = .043). Endoscopic balloon dilation was performed in 38.8% (95% confidence interval, 22.3–56.3%) of patients with benign strictures. Two perforations (1.3%) were reported as severe adverse events after double-balloon enteroscopy. A significantly lower surgery rate was found among cases with successful video capsule removal compared with unsuccessful cases (7.2% vs. 38.5%, p  = .002). Conclusions: Double-balloon enteroscopy is feasible and safe for removing retained video capsule endoscopes, and its use could decrease the need for surgery in patients with benign strictures and facilitate subsequent surgery in patients with malignant strictures.